Differences in contraceptive prices between and within family planning outlets in urban and semiurban Nigeria: a prospective cohort studyAJOG Global Reports at a Glance - Claire W. Rothschild, PhD, MS; Bo Hu, PhD; Justin Archer, MSc; Ekerette Emmanuel Udoh, MPH; Chinedu Onyezobi, MRPP; Anthony Nwala, MPH, MBA (Elsevier, 2022)
BACKGROUND: There is a lack of comprehensive evidence assessing variability and volatility in contraceptive prices. Improved understanding of contraceptive pricing, both between and within public and private service delivery points situated within complex, mixed health systems, may improve understanding of contraceptive access from the perspective of the consumer. OBJECTIVE: To describe variability and volatility in contraceptive method prices within localized urban and semiurban markets in Nigeria. STUDY DESIGN: We used product audit data from a complete census and longitudinal cohort of family planning vendors within 4 urban and semiurban study sites in Nigeria. Differences in outlet-level minimum prices by outlet type were assessed using generalized estimating equations. We presented descriptive summaries of within-outlet changes in minimum price over time. RESULTS: Among 672 family planning vendors, outlet-level minimum prices were significantly higher in private facilities/outlets than in public facilities. The outlet-level minimum price was $9.4 (95% confidence interval, $5.7-$13.2) higher for implants in private vs public facilities. We observed high availability of free contraceptive products in the public sector (79%-100%), moderate levels for specific contraceptive product types among community health workers and private facilities (28%-62% for male condoms), and low prevalence among private nonfacility outlets (0%-3%). Variability in contraceptive prices was high within private facilities and nonfacility outlets: standard deviations in the distribution of long-acting reversible contraceptive products ranged from $9.7 for implants to $13.1 for intrauterine devices in the private sector. Changes in minimum prices by contraceptive method type were common within the same outlets over time in the private sector. CONCLUSION: We observed high variability between and within contraceptive vendors in selected Nigerian family planning markets. Further research assessing the impact of price variability is critical for understanding contraceptive access and decision-making from the consumer's perspective.